Guía de aprendizaje para la conservación de la salud auditiva de los estudiantes de las clínicas odontológicas de la universidad Antonio Nariño (2021)
In accordance with the planned objectives, initially the frequency of discomfort caused by noise in the clinic of the Antonio Nariño university is confirmed, and that a large percentage of students have clear concepts about hearing protection, and this knowledge was expanded through the pedagogical guide obtaining 92% of students with clear concepts.